Differential Retinal Ganglion Cell Vulnerability, A Critical Clue for the Identification of Neuroprotective Genes in Glaucoma - Amin, Dwarkesh; Kuwajima, Takaaki (Frontiers in Ophthalmology, 2022)
Retinal ganglion cells (RGCs) are the neurons in the retina which directly project to the brain and transmit visual information along the optic nerve. Glaucoma, one of the leading causes of blindness, is characterized by elevated intraocular pressure (IOP) and degeneration of the optic nerve, which is followed by RGC death. Currently, there are no clinical therapeutic drugs or molecular interventions that prevent RGC death outside of IOP reduction. In order to overcome these major barriers, an increased number of studies have utilized the following combined analytical methods: well-established rodent models of glaucoma including optic nerve injury models and transcriptomic gene expression profiling, resulting in the successful identification of molecules and signaling pathways relevant to RGC protection. In this review, we present a comprehensive overview of pathological features in a variety of animal models of glaucoma and top differentially expressed genes (DEGs) depending on disease progression, RGC subtypes, retinal regions or animal species. By comparing top DEGs among those different transcriptome profiles, we discuss whether commonly listed DEGs could be defined as potential novel therapeutic targets in glaucoma, which will facilitate development of future therapeutic neuroprotective strategies for treatments of human patients in glaucoma.